Analysis of Product Demand Prediction Using Decision Tree on Sales Data of Ceria Toys Store - Anzas Ibezato Zalukhu; Muhammad Iqbal (Sean Institute, 2025)
Ceria Toys faces challenges in efficiently managing the inventory of electric bicycles, as product demand is influenced by factors such as market trends, seasons, and changing consumer preferences. To address this challenge, this research employs data mining techniques with the decision tree algorithm to predict product demand and assist in inventory management. The evaluation results of the predictive model show varying performance across product categories. The precision for the